Market Orientation of Industrial Enterprises - Shterev, Nikolai (Research Papers, 2010)
Creating good marketing skills is essential for the development of industrial business in a dynamic marketing environment and increasing the competition among manufacturers for both: users and resources. Industrial organizations are facing a number of market alternatives and the ability of managers for using market opportunities determine their actual market performance under these changing conditions.The main purpose to be achieved in the research paper is to identify those characteristics of the environment, which determine the level of industrial orientation to market requirements. The degree of market orientation is based on the relationship between environmental factors and management decisions. The research paper studies the following questions: What do market-oriented firms do better than non-market-oriented ones do?; How does market orientation implement in practice?; Which are the indicators for evaluating the level of market orientation?Finally, the paper gives some basic constant and variable factors which bring out a higher or lower degree of market orientation of industrial enterprises in Bulgaria.